2018
DOI: 10.1002/ca.23053
|View full text |Cite
|
Sign up to set email alerts
|

Femoral rotational asymmetry is a common anatomical variant

Abstract: The sulcus line (SL) is a three-dimensional landmark that corrects for individual variation in the coronal alignment of the trochlear groove in contrast to the traditional Whiteside's line (WL). Femoral rotational asymmetry (FRA) is an anatomical variation in which the posterior condyles and trochlear groove are not perpendicular to each other. This study aims to measure the SL and assess its reliability relative to WL, in addition to measuring and classifying the FRA. A retrospective analysis of a series of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The surgeon in the present study did not perform more than 15 procedures with NAVIO before enrollment of the patients, where Bell et al evidenced that learning curve was reached at 29 cases with NAVIO [ 37 , 38 ]. The increase in blood loss is not significant in the ra-TKA cohort and these results stands in the line with previously reported outcomes of avoiding of the intramedullary instrumentation [ 21 , 35 , 39 ]. Another study attributed it to saving the vascular structures by minimizing soft-tissue trauma and performing more precise bone cutting [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The surgeon in the present study did not perform more than 15 procedures with NAVIO before enrollment of the patients, where Bell et al evidenced that learning curve was reached at 29 cases with NAVIO [ 37 , 38 ]. The increase in blood loss is not significant in the ra-TKA cohort and these results stands in the line with previously reported outcomes of avoiding of the intramedullary instrumentation [ 21 , 35 , 39 ]. Another study attributed it to saving the vascular structures by minimizing soft-tissue trauma and performing more precise bone cutting [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Speaking about the importance of accurate femoral component rotational alignment, Newman et al found that knees have a high rate of rotational asymmetry, therefore to identify and classify the proper value by the case individually allows for the achievement of the best possible match to the patient’s anatomical variation [ 35 ]. Twiggs et al collected a cohort of 726 patients that appeared with multiple anatomic variations in the knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, patellofemoral complications after TKA remain common, mainly due to femoral component malpositioning [27]. Newman et al [19] revealed high variability of trochlear rotation in 191 non‐arthritic knees and concluded that the classification of trochlear rotation could yield tailored positioning of the femoral component. The larger trochlear rotation angles in Chinese and South African knees is therefore an important finding.…”
Section: Discussionmentioning
confidence: 99%
“…Rotational asymmetry is a concept that defines a divergence between the alignment of the extensor mechanism and the flexion–extension axis of the tibiofemoral joint [15, 21]. It has been described in relation to the femur by comparing the rotational alignment of the trochlear groove relative to the PC.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, in most femora, the rotational alignment of the PC is not perpendicular to the rotational alignment of the trochlear groove and that this asymmetry is linked to increasing degrees of varus angulation of the proximal tibial joint line [8, 22]. Given the highly variable association between the rotation of the trochlear groove and PC in normal femora [15], it is reasonable to hypothesise that there may be a relationship between PFI and femoral rotational asymmetry (FRA).…”
Section: Introductionmentioning
confidence: 99%